Impact of HIV-1, HIV-2, and HIV-1+2 dual infection on the outcome of tuberculosis - C. Wejse; C.B. Patsche; A. Kühle; F.J.V. Bamba; M.S. Mendes; G. Lemvik; V.F. Gomes; F. Rudolf (International Journal of Infectious Diseases, 2015)
Background: HIV-1 infection has been shown to impact the outcome of patients with tuberculosis (TB), but data regarding the impact of HIV-2 on TB outcomes are limited. The aim of this study was to assess the impact of HIV types on mortality among TB patients in Guinea-Bissau and to examine the predictive ability of the TBscoreII, a clinical score used to assess disease severity. Methods: In a prospective follow-up study, we examined the prevalence of HIV-1, HIV-2, and HIV-1+2 co-infection in TB patients in Guinea-Bissau, and the impact on outcomes at 12 months of follow-up. We included all adult TB patients in an observational TB cohort at the Bandim Health Project (BHP) in Guinea-Bissau between 2003 and 2013 and assessed survival status at 12 months after the start of treatment. Results: A total 1312 patients were included; 499 (38%) were female (male/female ratio 1.6). Three hundred and seventy-nine patients were HIV-infected: 241 had HIV-1, 93 had HIV-2, and 45 were HIV-1+2 dual infected. The HIV type-associated risk of TB was 6-fold higher for HIV-1, 7-fold higher for HIV-1+2 dual infection, and 2-fold higher for HIV-2 compared with the HIV-uninfected. Of the patients included, 144 (11%) died, 62 (12%) among females and 82 (9%) among males (hazard ratio (HR) 0.91, 95% confidence interval (CI) 0.64–1.30; p = 0.596). Compared to male patients, female patients were younger (1 year younger, 95% CI 0.5–2; p = 0.04), reported a longer duration of symptoms (14 days longer, 95% CI 4–25; p = 0.003), and had a higher TBscoreII (0.5 points more, 95% CI 0.3–0.7; p < 0.001). More females than males were HIV-infected (36% vs. 25%; p < 0.001) and more females had a body mass index (BMI) <15 kg/m2 (11% vs. 6%; p < 0.001) and a mid upper arm circumference (MUAC) <200 mm (13% vs. 7%; p < 0.001). HIV infection increased the mortality risk, with HIV-1 infection displaying the highest HR (5.0, 95% CI 3.5–7.1), followed by HIV-1+2 (HR 4.2, 95% CI 2.2–7.8) and HIV-2 (HR 2.1, 95% CI 1.2–3.8). A TBscoreII ≥4 was associated with increased mortality (HR 2.2, 95% CI 1.5–3.1). Significantly increased HRs were found for signs of wasting; a BMI <18 kg/m2 was associated with a HR of 1.8 (95% CI 1.3–2.6) and a MUAC <220 mm with a HR of 3.8 (95% CI 2.7–5.2). Conclusion: The HIV type-associated risk of TB was much higher for HIV-1 patients and higher but less so for HIV-2 patients, compared with the HIV-uninfected. Clinical severity at presentation was also higher for HIV-infected patients, although less so for HIV-2-infected patients, and all HIV-infected patients had a poorer outcome than the uninfected; mortality was 4–5-fold higher for HIV-1 and dually infected patients and two-fold higher for HIV-2-infected patients. These differences between HIV types did not disappear after adjusting for CD4 count.